2003
DOI: 10.1159/000071460
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lamivudine Therapy and Factors Associated with Emergence of Resistance in Chronic Hepatitis B Virus Infection in Japan

Abstract: Objective: Several reports have examined the efficacy of long-term lamivudine therapy and the risk factors involved in emergence of viral resistance in Japanese patients with hepatitis B virus (HBV) infection. However, the patient cohorts in such studies are relatively small. Methods: We analyzed 234 chronically HBV-infected Japanese patients who were treated with lamivudine for more than 12 months. They comprised patients with HBV genotype A (n = 8), genotype B (n = 21), genotype C (n = 203) and other HBV ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 33 publications
6
80
0
1
Order By: Relevance
“…Previous studies suggested that the HBV genotype, 14 the ALT level, 9,15 the degree of the decline of the HBV DNA level during therapy. 16,17 the presence of HBeAg, 15,18 the presence of core promoter mutations, 19 and HBV core-related antigens 20 were factors that could predict the emergence of YMDD mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the HBV genotype, 14 the ALT level, 9,15 the degree of the decline of the HBV DNA level during therapy. 16,17 the presence of HBeAg, 15,18 the presence of core promoter mutations, 19 and HBV core-related antigens 20 were factors that could predict the emergence of YMDD mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Using complex analysis, previous studies identified several factors predictive of emergence of YMDD mutants such as HBV genotype, 28 ALT level, 29,30 HBV DNA level before therapy, 28,[30][31][32] degree of decline of HBV DNA level during therapy, 33,34 presence of hepatitis B e antigen, 17,29,31,32,35 presence of core promoter mutations, 36 deletion of pre-S region, 37 and HBV core-related antigen. 38 We also showed that a slow decrease in HBV nucleic acid measured by the TMA-HPA is a marker of early emergence of mutants.…”
Section: Discussionmentioning
confidence: 99%
“…It potently inhibits HBV replication by interfering with the reverse transcriptase activity of the viral polymerase, which results in a marked decrease of HBV DNA and ALT levels, seroconversion of HBeAg to anti-HBe, and histopathological improvement 11 . However, one major problem with long-term use of lamivudine is the potential development of viral resistance, associated with increases in HBV DNA and serum transaminases 12 . The incidence of drug-resistant hepatitis B virus during lamivudine treatment is 14-36% after one year of treatment and increases to 38%, 49% and 66% after two, three and four years of treatment, respectively 13 .…”
Section: Methodsmentioning
confidence: 99%